The firm-specific determinants of cash holdings: evidence from China listed firms - WEN, SHIJIE (2017)
This paper investigates the firm specific predictors of corporate cash holdings for a sample of 716 China listed firms over the period from 2006 to 2013. The hypothesis raised on the basis of the trade-off model, the pecking-order theory as well as the free cash flow theory which are extensively used in previous researches. The results reveal that larger firms or firms with greater growth opportunities have preferences to accumulate cash while firms with higher leverage including a larger amount of bank debts, firms with more cash flows or firms pay dividends tend to hold less cash. However, the results also show evidence that financial distress and ownership are not important factors in determining cash holdings. Besides, I find that the overall effect of leverage, bank debt, cash flow and investment opportunity becoming weaker in the post-crisis period (2009-2013) and private firms’ cash holding policies are more sensitive to the financial crisis than state-owned enterprises’. This may be attributed to the tightening of external financial markets and meanwhile, creditors’ increased prudence of lending.